STUDENTS’ NEEDS ANALYSIS ON LEARNING OF THE ENGLISH LISTENING SKILLS IN VOCATIONAL HIGH SCHOOL - Sularti, Sularti; Drajati, Nur Arifah; Supriyadi, Slamet (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Learning English in Vocational High School has certain characteristics related to the learners' major. English as a foreign language has an important role to be mastered by the students. The orientation of the students after graduating from school mostly gets a job related to their competency. It is in line with the objective of the 2013 curriculum that learners of vocational high school are demanded to have a good character, an adequate competency, and be creative and innovative. As the mean of communication, English needs to be learned both in written and orally so that they can apply the English language in any situations after their graduation. This study aims at analyzing materials need in learning the English listening skills. The subjects of this study are twenty-three students from the eleventh grade of a vocational high school in Yogyakarta. The result of this research may help teachers and institutions preparing materials appropriately.